2015
DOI: 10.1111/apaa.12061
|View full text |Cite
|
Sign up to set email alerts
|

7 Dwelling on the Past: The Materiality of Everyday Life at Xaltocan, Mexico

Abstract: This chapter explores the materiality of dwelling on the remains of the past at Postclassic Xaltocan, Mexico, using household archaeology evidence. Such continued occupation in place evinced not only practical concerns of flood control, but also materialized an ethos of repetition and duplication in which reiterative practices created a ritually charged place, an ethos also seen at monumental sites such as the Aztec Templo Mayor. Dwelling on the past created a household landscape ripe with tlazolli, polluting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…As energized objects however, their visibility was not necessary for them to imbue spaces with power. As previously noted, it was common for Mesoamericans to incorporate vestiges of the past, including a variety of objects that might have qualified as tlazolli, into their religious and domestic structures (Overholtzer 2015). The ceramic fragments embedded in the wall foundations may reflect similar intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As energized objects however, their visibility was not necessary for them to imbue spaces with power. As previously noted, it was common for Mesoamericans to incorporate vestiges of the past, including a variety of objects that might have qualified as tlazolli, into their religious and domestic structures (Overholtzer 2015). The ceramic fragments embedded in the wall foundations may reflect similar intentions.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases outlined above, trash was made sacred by the context in which it was created or used. In other instances, however, trash appears to have had specific meaning or history that rendered it symbolically significant unto itself (Overholtzer 2015:95). This was probably the case with trash that was intentionally incorporated into socially meaningful places such as building walls.…”
Section: Trash and Sacred Contexts In Mesoamericamentioning
confidence: 99%
“…Living and acting in a house turn a house into a home (e.g., Chesson Moore 2012). The reiterative rebuilding of houses one on top of the other, which produces mounds and tells that form in the archaeological record, creates material connections with past houses (Overholtzer 2015). The wealth of ritual and religious objects commonly found in houses and workshops highlights how daily life is not opposed to ritual and religion but part of the process of the cocreation of belief systems (e.g., Bradley 2005, Fowles 2013, Kruczek-Aaron 2015, Stahl 2015.…”
Section: Everyday Life and Identitymentioning
confidence: 99%
“…Excavations on Structure 124 revealed that an imperial Aztec period single-room house was torn down and replaced by an extremely large house compound featuring three rooms, two interior patios, and two small storage rooms during the Colonial period. As in the Dehe phase renovations, excavations revealed significant spatial continuities in the placement and orientation of the dwellings constructed through time, and in the case of the colonial multiroom house, the previous single-roomed structure was replicated in nearly identical form as one of the rooms (Overholtzer 2015b). However, in each construction episode, the previous house was leveled and a new one was constructed; previous walls were not reused as was common in the earlier houses at the center of the island.…”
Section: The Dehe-hai Phase Transition At Xaltocan: Household Changesmentioning
confidence: 99%